2014
DOI: 10.1136/bjophthalmol-2013-304847
|View full text |Cite
|
Sign up to set email alerts
|

Ocular adnexal lymphoma: validation of American Joint Committee on Cancer seventh edition staging guidelines

Abstract: AJCC seventh edition T category was predictive of DFS in patients with OAL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
1
22
0
7
Order By: Relevance
“…Clinical stage of disease was assigned based on documented physical examination, complete blood count, bone marrow biopsy, MRI, CT, and positron emission tomography studies. Similar to the American Joint Committee on Cancer criteria for orbital lymphoma, for the purpose of this review, systemic lymphoma included local or distant metastasis or sites of involvement, lymphatic/nodal disease, and/or bone marrow disease . Given the similar staging of the American Joint Committee on Cancer criteria for paranasal sinus lymphoma with that of ocular, adnexal, and orbital lymphoma, data from this study were directly compared to that published in various studies by Demirci et al and Shields et al as a means of analytical reference.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical stage of disease was assigned based on documented physical examination, complete blood count, bone marrow biopsy, MRI, CT, and positron emission tomography studies. Similar to the American Joint Committee on Cancer criteria for orbital lymphoma, for the purpose of this review, systemic lymphoma included local or distant metastasis or sites of involvement, lymphatic/nodal disease, and/or bone marrow disease . Given the similar staging of the American Joint Committee on Cancer criteria for paranasal sinus lymphoma with that of ocular, adnexal, and orbital lymphoma, data from this study were directly compared to that published in various studies by Demirci et al and Shields et al as a means of analytical reference.…”
Section: Methodsmentioning
confidence: 99%
“…Because systemic lymphoma is a common malignancy, review of the literature reveals much preexisting research into its diagnosis, staging, management, and prognosis. Furthermore, lymphoma's common secondary manifestations, such as orbital and adnexal lymphoma, leave the literature concentrated with studies showing their particular prognoses and rates of systemic spread . On the other hand, because of sinonasal lymphoma's rarity, there have been limited attempts to examine the relationship between localized paranasal sinus lymphoma and systemic disease .…”
Section: Introductionmentioning
confidence: 99%
“…,b; Sniegowski et al. ). To obtain optimal therapeutic results in OAL, a structured diagnosis including detailed imaging of tumour localization, primary versus secondary manifestation, isolated ocular versus systemic manifestation, histology and antigenic characteristics is necessary (Kakkassery et al.…”
Section: Introductionmentioning
confidence: 97%
“…They can be classified via WHOcriteria histologically (diffuse versus nodular) and via cell-type (B-/T-and natural killer cells). Systemic staging is typically performed by Ann Arbor classification or alternatively via tumour, node, metastases (TNM)-classification (Coupland et al 2009a,b;Sniegowski et al 2014). To obtain optimal therapeutic results in OAL, a structured diagnosis including detailed imaging of tumour localization, primary versus secondary manifestation, isolated ocular versus systemic manifestation, histology and antigenic characteristics is necessary (Kakkassery et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Rath and colleagues in a similar and more recent study including 160 patients with POALs (Rath et al, 2014), conclude that the TNM base staging system better predicts outcome of POALs than the Ann Arbor system primarily by delineation of bilateral disease and nodal/metastatic involvement at presentation. Moreover, recently, Sniegowski et al in an important work validating the seventh edition staging guidelines of AJCC have found that AJC seventh edition T category was predictive of DFS with POAL (Sniegowiski et al, 2014).…”
Section: Stagementioning
confidence: 99%